A Study of Learning Achievement and Klui Pang-Aw Practical Skills of Grade 9 Students Using Flipped Classroom with Gamification - Nitmai, Pornsuda; Keeratichamroen, Dr.Wasana (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2023)
This research was aimed to 1) compare learning achievement on musical performance unit of grade 9 students using flipped classroom with gamification between before and after learning 2) compare learning achievement on musical performance unit of grade 9 students using flipped classroom with gamification after learning and the 70 percent criterion and 3) compare klui pang-aw practical skills on musical performance of grade 9 students using flipped classroom with gamification between before and after learning. The sample was selected using a cluster random sampling. The research instruments consisted of lesson plans, achievement test and klui pang-aw practical skills assessment form. The research findings showed that: 1) learning achievement was significantly higher than before learning at .05 level. 1) learning achievement was significantly higher than before learning at .05 level. and learning achievement was higher than the 70 percent criteria with no statistilly significant at .05 level. and 2) klui Pang-Aw practical was significantly higher than before learning at .05 level